A143 IMPACT OF A SIMULATION-BASED AUGMENTED REALITY CURRICULUM ON POLYPECTOMY SKILLS AMONG NOVICE ENDOSCOPISTS: A RANDOMIZED CONTROLLED TRIAL. (26th February 2020) - Khan, R; Scaffidi, M A; Gimpaya, N; Tham, D; Atalla, M; Al-Mazroui, A; Gholami, R; Satchwell, J B; Walsh, C M; Grover, S C
Abstract: Background: Polypectomy is an essential endoscopic skill. Training in polypectomy has been identified as a major deficiency for endoscopists worldwide as polypectomy occurs ad hoc during a colonoscopy when a polyp is detected, and a lack of standardized curricula. Augmented reality (AR), which superimposes computer-generated images on a user's view of the world, can address these gaps by standardizing encounters with polyps while completing simulated procedures and enabling polypectomy-specific teaching. Aims: Evaluate the impact of a simulation-based augmented reality curriculum on polypectomy performance among novice endoscopists. Methods: This study includes two cohorts of participants from 2019 to 2020. In 2019, participants were randomized into either: (1) a control curriculum, involving 6 hours of simulation-based training (SBT) supplemented by expert feedback, interlaced with 4 hours of small group teaching on the theory of colonoscopy; or (2) the augmented reality curriculum (ARC), in involving the same curriculum with integrated AR, wherein participants engaged with an AR-enhanced video demonstrating relevant therapeutic and pathologic details during polypectomy. The SBT for all participants involved a progressive curriculum starting on a bench-top model and then moving to the EndoVR® virtual reality simulator. The primary outcome was polypectomy-specific performance using the Direct Observation of Polypectomy Skills (DOPyS) tool during a simulated polypectomy after training, with a maximum score of 100. Results: Demographic characteristics are summarized in Table . In 2019, 21 novice endoscopists were enrolled. Immediately after training, the mean DOPyS score among ARC group participants was 76.2 (SD=17.9) compared to 71.8 (SD=13.2) among control group participants (Figure ). In this interim analysis, there was no significant difference between groups. Data analysis will be completed after 2020 participants complete the study. Conclusions: Interim results show a trend towards improved polypectomy performance with no significant difference. The results of this study have the potential to impact polypectomy education among novices. Simulation-based AR interventions may allow learners to progress towards achieving competency in polypectomy in a risk-free environment prior to first patient contact. Funding Agencies: None